2006
DOI: 10.1128/jvi.00879-06
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus Infection Activates the XBP1 Pathway of the Unfolded Protein Response To Cope with Endoplasmic Reticulum Stress

Abstract: The unfolded protein response (UPR) is a coordinated change in gene expression triggered by perturbations in functions of the endoplasmic reticulum (ER). XBP1, a key transcription factor of the UPR, is activated by an IRE1-mediated splicing event, which results in a frameshift and encodes a protein with transcriptional activity. Here, we report that XBP1 was activated during flaviviral infection, as evidenced by XBP1 mRNA splicing and protein expression, as well as induction of the downstream genes ERdj4, EDEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
203
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(219 citation statements)
references
References 73 publications
13
203
2
1
Order By: Relevance
“…Additionally, we find that mid-course during DENV infection (24 -36 h), the IRE1-XBP1 pathway is activated, as demonstrated by the presence of the sXbp1 mRNA and nuclear localization of XBP1, in agreement with previous reports for Japanese encephalitis virus and DENV (17). Activation of the IRE1-XBP1 pathway occurs during the phase of the viral life cycle in which protein synthesis and viral particle formation are taking place, causing both ER stress and phospholipid depletion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, we find that mid-course during DENV infection (24 -36 h), the IRE1-XBP1 pathway is activated, as demonstrated by the presence of the sXbp1 mRNA and nuclear localization of XBP1, in agreement with previous reports for Japanese encephalitis virus and DENV (17). Activation of the IRE1-XBP1 pathway occurs during the phase of the viral life cycle in which protein synthesis and viral particle formation are taking place, causing both ER stress and phospholipid depletion.…”
Section: Discussionsupporting
confidence: 79%
“…Other reports using the pestivirus bovine viral diarrhea virus have shown that induction of PERK and subsequent eIF2␣ phosphorylation induces the apoptotic pathway (16). Infection with Japanese encephalitis virus and DENV-2 was shown to induce the IRE-XBP1 pathway and a subset of XBP1-activated genes involved in the ER-associated degradation pathway, protecting cells from virus-induced cytopathic effects (17). In contrast, another group suggested that DENV induction of IRE1-XBP1 and ATF6 pathways contributed to dengue pathogenesis (18), whereas WNV induction of the UPR was shown to lead to CHOP-mediated apoptosis (19).…”
mentioning
confidence: 99%
“…Maintenance of moderately low levels of HCV in the infected liver may contribute to the persistence of HCV infection, often associated with a lengthy asymptomatic phase that can last for decades. A range of viruses, including flaviviruses such as JEV, dengue virus, and West Nile virus, have been reported to induce XBP1 mRNA splicing triggered by ER stress (2,3,24). However, we demonstrate here that, in contrast to HCV, the envelope protein of JEV, which causes acute encephalitis, is not recognized by EDEMs, and the ERAD pathway does not control JEV production.…”
Section: Discussionmentioning
confidence: 99%
“…Quality control of proteins, such as the elimination of misfolded proteins, is largely connected with the endoplasmic reticulum (ER), 2 which is an organelle responsible for the folding and distribution of secretory proteins to their sites of action. This pathway is termed ER-associated degradation (ERAD) and is triggered by ER stress.…”
Section: Viral Infections Frequently Cause Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…It also contains enzymes involved in drug and steroid metabolism. Several endogenous imbalances in cells, such as massive protein production, loss of calcium homeostasis, inhibition of N-linked glycosylation, and accumulation of mutant protein, often contribute to its malfunction (Yu et al 2006). One of the major morphological changes in Flavivirus-infected cells is the proliferation and hypertrophy of endoplasmic reticulum membranes, where virus particles accumulate inside (Barth 2000, Burke & Monath 2001, Hase et al 1992.…”
Section: Discussionmentioning
confidence: 99%